A novel hyperthermophilic methylglyoxal synthase: molecular dynamic analysis on the regional fluctuations - Gyo-Yeon Seo (Nature Portfolio, 2021)
Abstract Two putative methylglyoxal synthases, which catalyze the conversion of dihydroxyacetone phosphate to methylglyoxal, from Oceanithermus profundus DSM 14,977 and Clostridium difficile 630 have been characterized for activity and thermal stability. The enzyme from O. profundus was found to be hyperthermophilic, with the optimum activity at 80 °C and the residual activity up to 59% after incubation of 15 min at 95 °C, whereas the enzyme from C. difficile was mesophilic with the optimum activity at 40 °C and the residual activity less than 50% after the incubation at 55 °C or higher temperatures for 15 min. The structural analysis of the enzymes with molecular dynamics simulation indicated that the hyperthermophilic methylglyoxal synthase has a rigid protein structure with a lower overall root-mean-square-deviation value compared with the mesophilic or thermophilic counterparts. In addition, the simulation results identified distinct regions with high fluctuations throughout those of the mesophilic or thermophilic counterparts via root-mean-square-fluctuation analysis. Specific molecular interactions focusing on the hydrogen bonds and salt bridges in the distinct regions were analyzed in terms of interatomic distances and positions of the individual residues with respect to the secondary structures of the enzyme. Key interactions including specific salt bridges and hydrogen bonds between a rigid beta-sheet core and surrounding alpha helices were found to contribute to the stabilisation of the hyperthermophilic enzyme by reducing the regional fluctuations in the protein structure. The structural information and analysis approach in this study can be further exploited for the engineering and industrial application of the enzyme.